2006
DOI: 10.1007/s10800-006-9170-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal runaway of valve-regulated lead-acid batteries

Abstract: Valve-regulated lead-acid (VRLA) batteries that have aged on a float charge at constant voltage occasionally suffer from thermal runaway. Operating conditions for a VRLA battery have been simulated by changing the electrolyte saturation level in the separator and the ambient temperature. The charge current, battery temperature and cell overpressure were measured during current-limited constant-voltage charging. The experiments show that applied voltage, saturation level and ambient temperature are significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…3A, the lower part in saturation stratification charges efficiently than that in concentration stratification. In the period of the third charge (6 h till the end), the current in the upper part is higher because the rate of oxygen recombination is higher than that in the lower part, and partial current is consumed by oxygen evolution [29]. This can be seen from the electrode potential changes in Fig.…”
Section: Saturation Stratificationmentioning
confidence: 94%
“…3A, the lower part in saturation stratification charges efficiently than that in concentration stratification. In the period of the third charge (6 h till the end), the current in the upper part is higher because the rate of oxygen recombination is higher than that in the lower part, and partial current is consumed by oxygen evolution [29]. This can be seen from the electrode potential changes in Fig.…”
Section: Saturation Stratificationmentioning
confidence: 94%
“…In this failure mode, the chemical reaction rate within the cell increases uncontrollably, and the temperature of the battery increases in kind. This failure mode can result in fire or an explosion and, deservingly, has been the focus of substantial research [27][28][29].…”
Section: Battery Typesmentioning
confidence: 99%
“…Regarding thermal performance, the lead-acid battery failure mode in response to elevated temperatures is typically degradation in the performance of the cell [12]. Nonetheless, lead-acid batteries can experience thermal runaway when nearing the end of service life or when subjected to an excessively large float current [29].…”
Section: Lead-acidmentioning
confidence: 99%
“…In addition, the battery dehydration will increase the resistance of conductive channel, Joule heating, and decreasing the thermal capacity of battery. Hu et al [11] studied the relationship between dehydration and thermal runaway of battery, and found that the electrolyte saturation decreases as the degree of water loss (especially for the electrolyte saturation is less than 85%), and thus increasing the risk of thermal runaway significantly. The reason is that the oxygen diffusion resistance increase with the electrolyte saturation, due to the fewer gas channels left in this condition.…”
Section: "Water Loss" Of Batterymentioning
confidence: 99%